2016
DOI: 10.1016/j.memsci.2015.12.063
|View full text |Cite
|
Sign up to set email alerts
|

Ageing of polyvinylidene fluoride hollow fiber membranes in sodium hypochlorite solutions

Abstract: International audienceIn order to study the effect of cleaning operations on polyvinylidene fluoride (PVDF) hollow fiber membrane stability, ageing of two PVDF based membranes (one is additive free, the other contains hydrophilic additives) in contact with sodium hypochlorite solutions with various pH values has been studied. The aim of this experimental study was to identify the degradation mechanisms and to gain a better understanding of the effect of the (macro)molecular structure changes on the mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 35 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…In the work [ 32 ], dialysis membranes of PSf were treated with hypochlorite solution with an active chlorine concentration of 4% for 1 h. Based on the dextrans retention data, it was calculated that such treatment increased the effective pore size from 0.76 to 1.58 nm. Similar tendencies were observed for other polymeric membranes containing PVP as an additive, namely for polyethersulfone [ 28 , 34 , 35 , 36 , 37 ], polyvinylidene fluoride [ 38 , 39 ], cellulose acetate [ 40 ] and polyacrylonitrile [ 41 ]. Thus, it should be taken into consideration that exposure to sodium hypochlorite solution can modify PSf/PVP membrane properties.…”
Section: Introductionsupporting
confidence: 74%
“…In the work [ 32 ], dialysis membranes of PSf were treated with hypochlorite solution with an active chlorine concentration of 4% for 1 h. Based on the dextrans retention data, it was calculated that such treatment increased the effective pore size from 0.76 to 1.58 nm. Similar tendencies were observed for other polymeric membranes containing PVP as an additive, namely for polyethersulfone [ 28 , 34 , 35 , 36 , 37 ], polyvinylidene fluoride [ 38 , 39 ], cellulose acetate [ 40 ] and polyacrylonitrile [ 41 ]. Thus, it should be taken into consideration that exposure to sodium hypochlorite solution can modify PSf/PVP membrane properties.…”
Section: Introductionsupporting
confidence: 74%
“…Subsequently, the contact angle increased significantly after a soaking time of 2 weeks, indicating that prolonged exposure to NaOH changed the chemical structure of the membrane. Caustic cleaning agents have been reported to lead to dehydrofluorination phenomena, in which C=C bonds are formed when the H-F units are eliminated from the polymer [8,19]. Absorbance (a.u.)…”
Section: Naoh and Citric Acid Cleaningmentioning
confidence: 99%
“…Hollow-fiber membranes are usually pressurized in a housing or immerged in a basin and are mainly made of polyvinylidene fluoride (PVDF) or polyethersulfone (PES) [ 7 ]. PVDF is widely used as a polymeric membrane material due to its outstanding properties: i.e., high mechanical strength, flexibility, thermal stability, and chemical resistance [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies already observed different results depending on membrane modifications and retention compounds. Ravereau et al showed an increase in MS2 phages retention after membrane exposition to chlorine because of the increase in hydrophobicity of membrane surface [40]. Studies about retentions of bovine serum albumin (BSA) concluded on the enhancement of BSA retention with increase of membrane hydrophilicity, or BSA retention reduction with increase in membrane hydrophobicity [30,34,35].…”
Section: Membrane Ageingmentioning
confidence: 99%
“…Retention evolution with membrane ageing has already been assessed according to various compounds. Studies about organic compounds [37], E.coli and total bacteria [33,40], and bovine serum albumin (BSA) [30,34,35] retentions after chlorine exposure have given different results. Moreover, Ravereau et al observed MS2 retention and showed an increasing retention on aged membranes [40], when other studies at industrial scale observed a loss of 1 log in MS2 phage retention for 6 years-old membranes [19,25].…”
Section: Introductionmentioning
confidence: 99%